The importance of change management for BC First Nations' treaty implementation - Nyce, Harry (Author); Poff, Deborah (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2007)
This paper examines principles of change management and Treaty Agreements between First Nations in British Columbia and the governments of Canada and British Columbia. This combination is then examined to identify recommendations for Treaty implementation. --P.3. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1325931